2004
DOI: 10.1200/jco.2004.02.096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregnancy on Survival in Women With Cutaneous Malignant Melanoma

Abstract: The survival of pregnant women with melanoma is not worse than the survival of nonpregnant women with melanoma. Pregnancy subsequent to the diagnosis of primary melanoma was not associated with an increased risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
130
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(137 citation statements)
references
References 31 publications
4
130
3
Order By: Relevance
“…The results of uncontrolled studies conducted from 1950 to 1980 show that pregnancy is an unfavorable prognostic factor in patients' survival (Pack & Scharnagel, 1951;Sutherland et al, 1983;Trapeznikov et al, 1987 ), but the reports of recent controlled studies oppose this finding (Lens et al, 2004;Reintgen et al, 1985;McManamny et al, 1989;Wong et al, 1989;Slingluff et al, 1990;MacKie et al, 1991). The most recent population studies demonstrate equal survival among women with the same melanoma stage regardless they are pregnant or not (Lens et al, 2004;O'Meara et al, 2005). Overall survival rate in both pregnant and nonpregnant patients was 82% (Lens et al, 2004).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The results of uncontrolled studies conducted from 1950 to 1980 show that pregnancy is an unfavorable prognostic factor in patients' survival (Pack & Scharnagel, 1951;Sutherland et al, 1983;Trapeznikov et al, 1987 ), but the reports of recent controlled studies oppose this finding (Lens et al, 2004;Reintgen et al, 1985;McManamny et al, 1989;Wong et al, 1989;Slingluff et al, 1990;MacKie et al, 1991). The most recent population studies demonstrate equal survival among women with the same melanoma stage regardless they are pregnant or not (Lens et al, 2004;O'Meara et al, 2005). Overall survival rate in both pregnant and nonpregnant patients was 82% (Lens et al, 2004).…”
Section: Introductionmentioning
confidence: 76%
“…From 1958From to 1999 women with melanoma were included in the most extensive epidemiology study based on Swedish and regional registries; 0.9% of malignant melanomas were diagnosed during the pregnancy. Of all included patients, 5,533 of women were in reproductive age and 185 (3.3%) of them were diagnosed with melanoma during the pregnancy (Lens et al, 2004.). The prognostic features for melanoma depend on the stage it has been diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…A WHO study found a statistically increased tumor thickness in pregnant women versus non-pregnant controls, despite finding no impact of pregnancy on MM outcome [10]. Furthermore, a large population-based study found no significant difference in MM tumor thickness in pregnancy [11] and melanoma in pregnancy survival study showed the same [12]. Overall, there is little evidence to support that physiologic changes of pregnancy significantly affect the histopathology of MM.…”
Section: Prognosis For Women With Malignant Melanoma During Pregnancymentioning
confidence: 89%
“…Large-scale studies involving thousands of women have shown no significant correlation between localized melanoma diagnosis made during pregnancy and survival [11,12]. Some studies have shown a shortened disease-free interval in patients diagnosed in pregnancy, while other larger studies have shown no correlation.…”
Section: Prognosis For Women With Malignant Melanoma During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation